Analisis Strategi Guru dalam Meningkatkan Kemampuan Membaca Permulaan di Kelas 1 SD Bala Keselamatan Palu : Analysis of Teacher Strategies in Improving Beginning Reading Skills in Grade 1 of Palu Salvation Army Elementary School - Fatmilia Werangalu; Yun Ratna Lagandesa; Muhammad Aqil; Rangga Putera Boroallo; Rizal Rizal (ITScience (Information Technology and Science), 2026)
This study aims to describe the strategies a teacher employs to enhance the early reading skills of first-grade students at SD Bala Keselamatan Palu and to identify the factors that support and hinder their implementation. A qualitative descriptive approach was adopted, involving a first-grade teacher and 28 students (14 boys and 14 girls) as subjects. Data were collected through observation, interviews, and documentation, and subsequently analysed using the Miles and Huberman interactive model, which encompasses data collection, data reduction, data display, and conclusion drawing. Data validity was ensured through technique and source triangulation. The results indicate that the teacher implemented differentiated instruction using a